From Radio to X-Ray: Flares on the dMe Flare Star EV Lacertae - Osten, Rachel A; Hawley, Suzanne L; Allred, Joel C; Johns-Krull, Christopher M; Roark, Christine (The Astrophysical journal, 2005)
We present the results of a campaign to observe flares on the M dwarf flare star EV Lacertae over the course of two days in 2001 September, utilizing a combination of radio continuum, optical photometric and spectroscopic, ultraviolet spectroscopic, and X-ray spectroscopic observations to characterize the multiwavelength nature of flares from this active, single, late-type star. We find flares in every wavelength region in which we observed. A large radio flare from the star was observed at both 3.6 and 6 cm and is the most luminous example of a gyrosynchrotron flare yet observed on a dMe flare star. The radio flare can be explained as encompassing a large magnetic volume, comparable to the stellar disk, and involving trapped electrons that decay over timescales of hours. Flux enhancements at 6 cm accompanied by highly negatively circularly polarized emission ( pi sub(c) arrow right -100%) imply that a coherent emission mechanism is operating in the corona of EV Lac. There are numerous optical white-light flares, and yet no signature of emission-line response from the chromosphere appears. Two small ultraviolet enhancements differ in the amount of nonthermal broadening present. There are numerous X-ray flares occurring throughout the observation, and an analysis of undispersed photons and grating events reveals no evidence for abundance variations. Higher temperatures are present during some flares; however, the maximum temperature achieved varies from flare to flare. There is no evidence for density variations during any flare intervals. In the multiwavelength context, the star of the intense radio flare is coincident with an impulsive optical U-band flare, to within 1 minute, and yet there is no signature of an X-ray response. There are other intervals of time when optical flaring and UV flaring is occurring, but these cannot be related to the contemporaneous X-ray flaring: the time-integrated luminosities do not match the instantaneous X-ray flare luminosity, as one would expect for the Neupert effect. We investigate the probability of chance occurrences of flares from disparate wavelength regions producing temporal coincidences but find that not all the flare associations can be explained by a superposition of flares due to a high flaring rate. We caution against making causal associations of multiwavelength flares based solely on temporal correlations for high flaring rate stars such as EV Lac.